Impact of E-logistics Service Quality on Customer’s Satisfaction and Loyalty: Evidence in Hanoi, Vietnam - Ta Thi Yen; Nguyen Thi Thuy Trang; Tran Tuan Anh (East Asian Journal of Multidisciplinary Research, 2022)
The study assesses service quality and customer loyalty among logistics service providers, with customer satisfaction acting as a moderator between these factors. The survey questionnaire was used to acquire 401 data points from Vietnamese consumers. Least-squares technique was used to examine the data (PLS-SEM). According to the findings, service quality characteristics such as customer service, product quality, information quality, delivery service, perceived pricing, and reverse logistics all have a beneficial impact on customer loyalty via customer satisfaction. According to the findings, customer pleasure is directly related to client loyalty. According to the report, service providers should modernize and improve the quality of their services.